Nanosuspension: Newer Approach for Drug Delivery System - Mittal, Priyanka; Singh, Preeti; Verma, Anamika; Khinchi, M. P.; Agarwal, Dilip; Gupta, M. K.; Singh, S. P. (Asian Journal of Pharmaceutical Research and Development, 2013)
Nanotechnology is defined as science and engineering carried out in a nanoscale that is 1-1000nm.Critical problem of poorly soluble drugs is low bioavailability and erratic absorption. The problem is even more complex for drugs belonging to biopharmaceutical classification system BSS CLASS2 category such as Carbamezepine and Intraconazole, as they are poorly soluble in both aqueous and non aqueous media. Nanosuspensions are biphasic systems consisting of pure drug particles dispersed in an aqueous vehicle, stabilized by surfactants. Nanosuspension technology can be used to improve the stability as well as bioavailability of poorly soluble drugs. It consists of pure poorly water soluble drug without any matrix material suspended in dispersion. Nanosuspensions can be delivered by oral, parental, pulmonary and ocular routes. A Nanosuspension not only solves the problems of poor solubility and bioavailability but also alters the pharmacokinetics of drugs and thus improves drug safety and efficacy. These are simple to prepare and are more advantageous than other approaches. Techniques such as wet milling, high pressure homogenization, emulsification-solvent evaporation and supercritical fluid have been used in the preparation of Nanosuspensions